Compaction of LiBH4-MgH2 doped with MWCNTs-TiO2 for reversible hydrogen storage. (12th January 2017) - Plerdsranoy, Praphatsorn; Chanthee, Songwuit; Utke, Rapee
Abstract: According to catalytic effects of TiO2 on kinetic properties of hydrides and thermal conductivity of multiwall carbon nanotubes (MWCNTs) favoring heat transfer during de/rehydrogenation, improvement of dehydrogenation kinetics of compacted 2LiBH4 -MgH2 by doping with MWCNTs decorated with TiO2 (MWCNTs-TiO2 ) is proposed. Via solution impregnation of Ti-isopropoxide on MWCNTs and hydrothermal reaction to produce TiO2, high surface area and good dispersion of TiO2 on MWCNTs surface are obtained. Composite of 2LiBH4 -MgH2 is doped with 5–15 wt. % MWCNTs-TiO2 and compacted into the pellet shape (diameter and thickness of 8 and 1.00–1.22 mm, respectively). By doping with 15 wt. % MWCNTs-TiO2, not only fast dehydrogenation kinetics is obtained, but also reduction of onset dehydrogenation temperature (Δ T = 25 °C). Besides, gravimetric and volumetric hydrogen storage capacities of compacted 2LiBH4 -MgH2 increase to 6.8 wt. % and 68 gH2 /L, respectively, by doping with 15 wt. % MWCNTs-TiO2 (∼twice as high as undoped sample). The more the MWCNTs-TiO2 contents, the higher the apparent density (up to ∼1.0 g/cm 3 by doping with 15 wt. % MWCNTs-TiO2 ). The latter implies good compaction, resulting in the development of volumetric hydrogen capacity. In the case of mechanical stability during cycling, compacted 2LiBH4 -MgH2 doped with at least 10 wt. % MWCNTs-TiO2 maintains the pellet shape after rehydrogenation. Although increase of porosity (up to 30%), leading to the reduction of thermal conductivity, is detected after rehydrogenation of compacted 2LiBH4 -MgH2 doped with 15 wt. % MWCNTs-TiO2, comparable kinetics during cycling is obtained. This benefit can be achieved from thermal conductivity of MWCNTs. Highlights: First time compaction of 2LiBH4 -MgH2 doped with MWCNTs-TiO2 . Faster dehydrogenation kinetics as compared with undoped sample. 75–77% of theoretical H2 capacity after doping with MWCNTs-TiO2 and compaction. Volumetric H2 capacity up to 68 gH2 /L after doping with 15 wt. % MWCNTs-TiO2 . Good mechanical stability during cycling by doping at least 10 wt. % MWCNTs-TiO2 .